DIGITAL RELIGION AND VIRTUAL COMMUNITIES: A BIBLIOMETRIC REVIEW OF ONLINE RELIGIOUS PRACTICES - Ratu Syifa Alrissa; Winoto, Yunus; Khadijah, Ute Lies Siti (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2025)
Technological transformation has affected every aspect of human life, including the way individuals and communities conduct their spiritual activities. This phenomenon, known as digital religion, has become increasingly prevalent in society. Recently, numerous scientific studies have been conducted on the topic of digital religion and virtual communities. This study analyzes digital religion and virtual communities using a bibliometric approach, employing the Biblioshiny R programming application and data from Scopus, spanning the period from 2011 to 2024. The resulting dataset comprises 31 scientific articles, which were then extracted and summarized. The results showed a fluctuating production of articles on the topic of digital religion and virtual communities each year, with the highest production occurring in 2024 when a total of 7 scientific articles were published. Meanwhile, the average number of citations for scientific articles occurred in 2011. Sweden dominates in the contribution of articles and citations, while the United States occupies a position slightly below it. The top researchers in this field are Alfonso, I. B and Buesa, M. G. The journal with the most publications is Jenkins H. Convergence Culture. The major trends and thematic clusters reflect the picture related to digital religion and virtual communities. This research makes a significant contribution to understanding the development of digital religion and virtual communities research through bibliometric analysis. This research can serve as a strategic guide for future researchers who will delve deeper into this topic.